Analysis And Classification Of Alcoholics Using Single Trials Of Visual Evoked Potential Signals - P., Sharmila Kanna (2004)
In this thesis, analysis and classification of alcoholics is conducted using single trials of Visual Evoked Potential (VEP) signals extracted from the scalp during the perception of visual stimulus. A problem with the analysis of VEP signals is the corruption from ongoing electroencephalogram (EEG) and noise artifacts. VEP signals are relatively lower in signal strength as compared to EEG and therefore, the EEG distorts the VEP signal.